(untitled) (Advancements in Homeopathic Research, 2022)
Aim & Objective: To study the efficacy of individualized Homoeopathic Treatment in patients suffering from chronic low back pain and to assess change in their quality of life (QOL) Methods: It was a single-centred, prospective, interventional study conducted at MNR UHC Homeopathic OPD in Sangareddy, from Nov 2018 to April 2019. At 0 day (Baseline) and 180 days standardized measuring scale were used like, Oswestry Disability Index, SF-12 questionnaire. The primary outcome was to improve the symptoms by reducing the pain at the end of 180 days of treatment. The secondary outcome was to assess the quality of life of patients treated with homoeopathic medication using SF-12 health status questionnaires for quality of life. Total 25 patients were screened during the study period. Results: Estimation of the Oswestry Disability Index showed that: severity of pain, personal care, sitting, standing, social life and travelling score were significantly improved (P<0.05). Significant differences were also found in the Quality of Life (QOL) SF 12 in physical domain [difference 24 (95% CI: -6.77, -0.51)], and psychological domain [difference 24 (95% CI: - 7.17, -0.91] (p < 0.05). Conclusion: Homoeopathic treatment has made significant improvement in the patients suffering from chronic low back pain pertaining to the symptom’s severity and overall perception of QOL in physical and psychological domains. Further Randomised control trail can be conducted for validation of the results.